Severe Skin Diseases in Children Beyond Topical Therapy - Tom, Wynnis L.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Children are no less spared from severe skin diseases. This textbook is designed as a practical clinical reference that will guide practitioners in treating difficult dermatoses in children in whom topical therapy has been unsuccessful. Individual sections are devoted to inflammatory diseases, immune-mediated/autoimmune diseases, tumors and proliferative disorders, and genodermatoses. Each chapter addresses which patients represent suitable candidates for systemic or other non-topical therapy and considerations and caveats in the use of such approaches. Potential treatments are then appraised from a current evidence-based perspective, with provision of detailed but relevant information and reference tables that summarize recommendations in use and monitoring. Future directions in management are also presented.
Inflammatory Diseases:- Immune-Mediated/Autoimmune Diseases -- Photosensitive Disorders -- Tumors -- Genodermatoses -- Appendix.
Keywords: Medicine; Dermatology; Medicine & Public Health; Dermatology